Conversion of Foreign Currency Loans in the CEECs (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Between 2004 and 2008 low-interest foreign currency based loans, and above all household loans, became more and more popular in Central European countries like Croatia, Hungary, Poland, Romania and the Baltic countries in an environment of high and volatile inflation but stabilising and in some cases appreciating exchange rate. (Király–Simonovits, 2015) The stable outlook for the exchange rate was further strengthened by the prospect of euro adoption. When the global financial crisis hit Europe, however, Central European economies went under a strong currency depreciation and decline in income, interest and principal payments put a much greater burden on debtors than previously. The situation was further deteriorated by the decision of the Swiss National Bank to abandon the cap of its currency’s value against the euro. After the comparison of the extent of depreciation and the dynamics of household FX loans based on central bank data, the paper examines the economic policy measures taken by Croatia, Hungary, Poland and Romania to protect debtors from the increasing debt burden with special emphasis on the leading role of the Central Bank of Hungary (MNB) having been widely acknowledged by international organisations (IMF, 2016, European Commisson, 2016a).This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.